Prevalence and Risk Factors of Anxiety in a Clinical Dutch Sample of Children with an Autism Spectrum Disorder - Wijnhoven, Lieke A. M. W.; Creemers, Daan H. M.; Vermulst, Ad A.; Granic, Isabela (Frontiers in Psychiatry, 2018)
Anxiety is highly prevalent in children with an autism spectrum disorder (ASD). However, there is inconsistency in studies investigating prevalence and risk factors of anxiety in children with ASD. Therefore, the first aim of the present study was to give an overview of the prevalence of anxiety symptoms in a clinical Dutch sample of children with ASD. The second aim was to investigate age, gender, ASD subtype and IQ as potential risk factors for anxiety in this sample. In total, 172 children with ASD (8-15 years) and their parents participated in the present study. Specialized services in which children with ASD were recruited were two mental health institutes and one secondary special education school. The findings showed that more than 60% of the participating children with ASD had at least subclinical anxiety symptoms according to children. More than 80% of the children with ASD had at least subclinical anxiety symptoms according to parents. It was found that younger children and girls with ASD had more anxiety symptoms than older children and boys with ASD. Moreover, it was found that children with a higher PIQ and lower VIQ had more specific phobia symptoms. The findings suggest that in a clinical context, children with ASD have a high risk to have co-occurring anxiety symptoms, especially girls and younger children with ASD. Therefore, early prevention and treatment of anxiety in children with ASD who are most at risk is important.